Assessment of Mindanao Agriculture sector's performance - Axalan, Jerick T.
The study aimed to assess the agriculture performance of Mindanao as measured by its GRDP in agriculture. Selected variables such as GVA in crops, fishery, poultry, livestock, and forestry; trade in agriculture (export and import); employment in agriculture; budget allocation in agriculture; agricultural loans; real wage rate in agriculture; and population were used as factors affecting the performance of Mindanao's agriculture sector. The study tried to probe more on the underlying factors behind the performance of the selected variables. Furthermore, it also attempted to find out which of those factors significantly affect the performance of the GRDP in agriculture. The study employed descriptive analysis (value, percentage share, growth rate, and trend), which was based on the secondary data gathered in government, non-government agencies, and other sources. Furthermore, quantitative analysis (correlation) was made to find out the degree of relationship between the variables and the GRDP in agriculture. The study found out that the main source of growth of Mindanao GRDP in agriculture were the crops and fishery sectors- particularly rice, corn, and banana among the crops and commercial and aquaculture sub-sectors in the fishery sector. They also posted high correlation with the GRDP in agriculture. Other variables except the imports in agriculture also portrayed high correlation with the GRDP in agriculture. Thus, most of the variables used did affect the performance of Mindanao's agriculture sector. Policy implications were also discussed in this study. Though this study was broad enough to capture the whole aspects of the Mindanao's agriculture sector, the proponent would still recommend further analysis involving other factors like investment, infrastructure, policies, and other variables. Moreover, it is recommended to update the time period or replicate study on a regional basis.